Reoperation for Pyriform Sinus Fistula in Pediatric Patients - Sheng, Qingfeng; Lv, Zhibao; Xu, Weijue; Liu, Jiangbin (Frontiers in Pediatrics, 2020)
Introduction: The aim of this study was to analyze the authors’ experience in re-operative surgery for children with PSF who were subjected to attempted but failed operations. Methods: We retrospectively analyzed the medical records of 30 patients with PSF who underwent re-operation (i.e., a revision of the primary performed definitive procedure) from Jan 2010 to Dec 2018. Results: There were 19 boys and 11 girls. 29 cases were left-sided. The median age of patients underwent the primary operation was 5.5 years (range, 15 days-14 years). Five children received two definitive procedures from outside hospitals. The primary operations included traditional open-neck surgery (n=30), endoscopic-assisted open-neck surgery (n=4), endoscopic laser cauterization (n=1). The median time from primary operation to recurrence was 4 months (range 1 month-4 years). The reasons for recurrence were incomplete resolution of infection (n=7), incomplete resection of the fistula (n=23), cauterization of PSF inner orifice (n=1), only cyst excision in neonates (n=2), unknown (n=2). All 30 children underwent endoscopy-assisted open-neck surgery. The median age of children underwent re-operation was 8 years (range, 2 years-17 years). The fistula was detected in 29 cases (96.7%). After re-operation, good outcome was achieved in 27 patients (90%). Wound infection developed in one case. PSF recurred in 2 cases (6.7%). Conclusion: Most recurrence observed by us are preventable. Complete resolution of infection, clear verification and exact resection of the fistula at a high level are essential for preventing recurrence. Endoscopy-assisted surgery is effective for PSF reoperation.